Public Private Partnership Models for Women Entrepreneurship Development in Agriculture (Global Journal of Science Frontier Research, 2014)
The paper contributes empirical evidence on the status of Public-Private Partnership models (PPP) for rural women entrepreneurship development through Self Help Groups (SHGs) in agriculture and classifies them based on the concept of value creation. The study was conducted in Kerala, India during 2009-12, where women entrepreneurship development in agriculture through SHGs is rampant. Ex-post facto design was used to collect data from a purposive sample of 1400 from the four regionally representative zones of the state. Weighted score and case study methods were used in the selection and classification of the delineated models. Study identified 466 women development projects with PPP components. From this 22 cases with working PPP elements were selected for detailed analysis using a weighted score method. Six models with high scores viz Cadbury-KAU Cooperative Cocoa Research Project, Thirumadhuram Pineapple Project, Uravu RSVY Micro Enterprises Project, Sevashram Organic Producer Company, Subicsha Coconut Producers' Company Ltd and Nendran Banana (Samagra) Project were used for detailed case study. The major public and private agencies involved and focus domains were delineated.
Keywords: value creation; self help groups; women empowerment; social enterprises; public welfare model; private employment model